Corporate social responsibility, earnings management, and firm performance: Are the companies really ethical?. Issue 1 (July 2021) - Widagdo, A.K.; Murni, Sri; Nurlaela, Siti; Rahmawati,
Abstract: Climate change challenges present organizations (e.g., companies, corporations, nongovernmental organizations (NGOs)), communities, and citizens with the need to redefine current views on corporate social responsibility (CSR) from a voluntary luxury as being a necessity. CSR can be an effective tool for mitigating climate change. Firms have to redress climate change through environment-friendly manufacturing techniques, adopting a green, transparent policy and environmental disclosure. Based on the extant literature, CSR activities can create a positive image for the company and increase company value. However, some scholars also argue that CSR activity may also be used to hide the opportunistic behaviour of management, namely earnings management. Therefore, the purpose of this study is to examine the relationship between CSR and a firm's performance and the moderating role of earnings management on the relationship between CSR and firm performance. The sample of this research is the mining sector because this sector is included in a high-profile company, which is vulnerable to environmental damage issues. The period of observation is 2015-2019. The method of analysis uses the panel data method. The results indicate that CSR has a positive and significant relationship with a firm's values. In addition, earnings management does not moderate the relationship between CSR and a firm's value. It indicates that earnings management is not a moderating variable but a predictor variable/independent variable. The finding implies that the firms do not make social responsibility activities a symbolic activity used as a means by management to cover earnings management activities.